PELATIHAN REGULASI EMOSI UNTUK MENURUNKAN PERILAKU AGRESIF PADA ANAK - Syahadat, Yustisi Maharani (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstractThis study focused on the aggressive behavior of child in elementaryÂ school, and efforts to cope the aggressive behavior. This research usedÂ the emotion regulation training that aims to determine about the influenceÂ of emotion regulation training against aggressive behavior in schoolâs child.Â The hypothesis in this study was emotion regulation training influential toÂ reduce aggressive behavior of child in fifth grade and ten years old. ThisÂ research used a Single Case Experimental Design by âA-B with singletargetÂ measure and follow-upâ models. Research subjects were twoÂ elementary school students, aged 10 years, who had aggressive behavior.Â Training of emotion regulation was done over the fiveconsecutive sessions,Â and observed aggressive behavior during the six days before training (phaseA), six days after training (phase B) and four days at follow-up. ObservationÂ results were analyzed with a visual inspection technique using a graph, andÂ showed there is reduction in aggressive behaviorâs subject at phase BÂ after emotion regulation training. The results obtained showed that emotionregulation training can reduce aggressive behavior for child in elementaryÂ school according to the criteria of the subject.Keywords: emotion regulation training, aggressive behavior of schoolâsÂ child.